Expression patterns of CD56+and CD16+cells in renal transplant biopsies with acute rejection: Associations with microcirculation injuries and graft survival - Dos Santos, Daniela Cristina [UNESP]; Saraiva Camara, Niels Olsen; Ribeiro David, Daisa Silva; Avancini Costa Malheiros, Denise Maria (Wiley-Blackwell, 2017)
BackgroundThe study investigated whether immunohistochemical features of interstitial and glomerular CD56 and CD16 infiltrates - NK cells markers - could be associated with microcirculation injury scores - peritubular capillaritis (ptc) and glomerulitis (g) - and graft survival. MethodsThe research analyzed the immunohistochemical pattern of CD56 and CD16 in interstitial and glomerular compartments of biopsies for-cause biopsies from 59 recipients diagnosed with acute rejection (mean=135.5days post-transplant). ResultsInterstitial CD56+ cells had an increased expression for glomerulitis (g1) (P=0.02) and peritubular capillaritis (ptc2) (P=0.003) presence. It was noted that interstitial CD56+cells with mean above 0.56cells/mm(2) had worse allograft survival. CD56+ cells in the interstitial compartment with mean less than or equal to 0.56cells/mm(2) was related with absence or mild peritubular capillaritis (P=0.012) and mean above 0.56cells/mm(2), respectively, with glomerulitis (P=0.002) presence. Interstitial CD16 cells showed greater positive results in relation to peritubular capillaritis (P=0.0001) cases. Similarly, it was observed that glomerular CD16+ cells had higher positive results in glomerulitis (P=0.009) presence. ConclusionsThe study findings showed that CD56+ cell infiltrated in the interstitial compartment was significantly associated with microcirculation injury scores, especially the glomerulitis, and graft survival. Summary at a Glance This study suggests that increased expression of interstitial natural killer cells in renal allograft biopsies of kidney transplant recipients with rejection may be associated with poorer graft outcomes.
Keywords: immunostaining; microcirculation injury; Natural Killer cells; renal allograft survival; renal pathology; transplant